2006
DOI: 10.1167/iovs.05-1407
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Protects Retinal Ganglion Cells from Pressure-Induced Death

Abstract: For RGCs at ambient pressure, IL-6 secreted from astrocytes and microglia under pressure is adequate to abate other proapoptotic signals from these glia. For RGCs challenged by elevated pressure, decreased IL-6 in astrocyte medium is insufficient to counteract these signals. Increased IL-6 in microglia medium counters not only proapoptotic signals from these cells but also the pressure-induced apoptotic cascade intrinsic to RGCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
160
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(177 citation statements)
references
References 77 publications
15
160
1
Order By: Relevance
“…Rises in IL-6 suppress pro-apoptotic signalling pathways and cell death. 45 Therefore, provided strategies can be devised to selectively induce increases in microglial TRPV1 channels expression, TRPV1 channels may be a potential drug target in managing pressure-induced retinal ganglion cell loss in glaucoma.…”
Section: Roles Of Trp Channels In Glaucomamentioning
confidence: 99%
“…Rises in IL-6 suppress pro-apoptotic signalling pathways and cell death. 45 Therefore, provided strategies can be devised to selectively induce increases in microglial TRPV1 channels expression, TRPV1 channels may be a potential drug target in managing pressure-induced retinal ganglion cell loss in glaucoma.…”
Section: Roles Of Trp Channels In Glaucomamentioning
confidence: 99%
“…Previous research indicates that inflammatory responses in the retina, including glial cell activation and production of inflammatory cytokines [5][6][7][8][9][10][11][12][13][14][15][16][17][18], play a role in glaucomatous degeneration of RGCs. These inflammatory responses can be either detrimental or neuroprotective for RGCs challenged by glaucomatous stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated pressure is a significant risk factor (2,3). Although the role of glial cells in glaucomatous retinae remains under debate, certain research has found that the expression of various genes by Müller cells can be altered in glaucomatous models, including the glial fibrillary acidic protein (GFAP), glutamine synthetase (GS) and nestin (1,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…T75 culture flasks, equipped with manometers, were placed in incubators and maintained at 37˚C, as the pressure mechanism, as described in detail in our previous study (3). A mixture of 95% air and 5% CO 2 was pumped into the flasks to obtain the pressure (2). To determine the short-term effects of elevated pressure on the Müller cells, we exposed our cultures to a wide range of pressures (20,40, 60 and 80 mmHg).…”
Section: Introductionmentioning
confidence: 99%